2020
DOI: 10.21468/scipostphys.8.2.016
|View full text |Cite
|
Sign up to set email alerts
|

Current operators in integrable spin chains: lessons from long range deformations

Abstract: We consider the finite volume mean values of current operators in integrable spin chains with local interactions, and provide an alternative derivation of the exact result found recently by the author and two collaborators. We use a certain type of long range deformation of the local spin chains, which was discovered and explored earlier in the context of the AdS/CFT correspondence. This method is immediately applicable also to higher rank models: as a concrete example we derive the current mean values in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
98
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 68 publications
(107 citation statements)
references
References 54 publications
(109 reference statements)
9
98
0
Order By: Relevance
“…for some α also generates quasi-local charges. This deformation was treated in detail in [24], where it was shown that the κ-derivative of the charges is…”
Section: The Charges Continue To Form a Commuting Familymentioning
confidence: 99%
See 4 more Smart Citations
“…for some α also generates quasi-local charges. This deformation was treated in detail in [24], where it was shown that the κ-derivative of the charges is…”
Section: The Charges Continue To Form a Commuting Familymentioning
confidence: 99%
“…For simplicity we restrict ourselves to systems with a simple (non-nested) Bethe Ansatz; the extension to nested cases is rather straightforward (c.f. [21,24]). Furthermore, we do not specify the details of the model; concrete formulas pertaining to the XXX and XXZ models can be found for example in [27,24].…”
Section: Action On Bethe Statesmentioning
confidence: 99%
See 3 more Smart Citations